A study of the influence of visual imagery on graphic design ideation. (July 2016) - Laing, Simon; Masoodian, Masood
Abstract : Although existing literature shows that graphic designers collect and access visual imagery as part of their design process, the influence of such material on the process of ideation and the creative output of design is generally unclear. Therefore, we carried out a study with 18 graphic design students to better understand the effects of supplying specific types of images during the ideation phase on the creative outputs of the graphic design process. The findings demonstrate that exposure to the images had minimal measurable effect on the creativity of the design outputs, as rated by experts judges and study clients. The participants, however, reported positive benefits from the availability of visual images to their experience during the ideation phase of the design process. Highlights: Seeing client and market images during ideation has minimal effect on creativity. Such images shown to positively effect participants' experience of the process. Designer seeing client aesthetic images may increase client acceptance of outputs.